2013
DOI: 10.1371/journal.pone.0068292
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Seasonal Flexibility in Avian Metabolic Performance Highlights the Uncoupling of Basal Metabolic Rate and Thermogenic Capacity

Abstract: Stochastic winter weather events are predicted to increase in occurrence and amplitude at northern latitudes and organisms are expected to cope through phenotypic flexibility. Small avian species wintering in these environments show acclimatization where basal metabolic rate (BMR) and maximal thermogenic capacity (MSUM) are typically elevated. However, little is known on intra-seasonal variation in metabolic performance and on how population trends truly reflect individual flexibility. Here we report intra-sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
76
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 54 publications
9
76
1
Order By: Relevance
“…The Ṁ sum increases with cold acclimation for juncos in this study also fit into the lower end of the seasonal range of Ṁ sum variation for small birds in temperate-zone climates, with summer to winter increments generally in the 10-50% range (Swanson, 2010). The colder minimum temperatures and increased temperature variability encountered by wild birds in cold winter climates probably result in generally higher seasonal Ṁ sum increments relative to the cold acclimation protocol in this study, as Ṁ sum varies with temperature [higher during colder winters (Swanson and Olmstead, 1999;Petit et al, 2013)] and with temperature variability (Vézina et al, 2006;Vézina et al, 2011).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The Ṁ sum increases with cold acclimation for juncos in this study also fit into the lower end of the seasonal range of Ṁ sum variation for small birds in temperate-zone climates, with summer to winter increments generally in the 10-50% range (Swanson, 2010). The colder minimum temperatures and increased temperature variability encountered by wild birds in cold winter climates probably result in generally higher seasonal Ṁ sum increments relative to the cold acclimation protocol in this study, as Ṁ sum varies with temperature [higher during colder winters (Swanson and Olmstead, 1999;Petit et al, 2013)] and with temperature variability (Vézina et al, 2006;Vézina et al, 2011).…”
Section: Discussionsupporting
confidence: 58%
“…Petit et al (Petit et al, 2013) also documented inter-and intra-seasonal variation in Ṁ sum in blackcapped chickadees Poecile atricapillus consistent with a proximate role for temperature in mediating thermogenic capacity. Moreover, cold acclimation in captive red knots Calidris canutus over a complete annual cycle with natural photoperiod resulted in elevated Ṁ sum compared with warm acclimation, and warm-acclimated birds failed to show elevated thermogenic capacity during the winter photoperiod, although Ṁ sum did increase during the spring migration period (Vézina et al, 2011).…”
Section: Discussionmentioning
confidence: 82%
“…Here, we refer to any physiological adjustment of an organism in response to an environmental stimulus resulting in the improved ability of that organism to cope with its changing environment as physiological adaptation (Boratynski et al, 2017;Brinkmann et al, 2014;Rymer et al, 2016). However, physiological adaptation is also often called acclimatization (Noakes et al, 2017;Petit et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, both Sharbaugh (Sharbaugh, 2001) and Liknes and Swanson (Liknes and Swanson, 2011) showed increases in body mass in wintering chickadees relative to their summer counterparts. This species is also known to improve its metabolic performance in winter relative to summer (Cooper and Swanson, 1994;Lewden et al, 2012;Petit et al, 2013). For instance, using birds from the same population, Petit et al (Petit et al, 2013) reported that chickadees elevated their winter Ṁ sum by 25% between the beginning (October) and the peak of winter (February).…”
Section: Discussionmentioning
confidence: 99%
“…Because pectoral muscles are the largest muscles in birds (Marsh and Dawson, 1989;Swanson, 1991b;O'Connor, 1995), it is widely assumed that the increase in Ṁ sum typically seen in cold-acclimatized birds (O'Connor, 1995;Cooper, 2002;Petit et al, 2013) results from the associated increase in pectoral muscle size (Cooper, 2002;Saarela and Hohtola, 2003;Vézina et al, 2007;Vézina et al, 2011), and recent findings by in American goldfinches (Spinus tristis) support this interpretation. However, the link between Ṁ sum and the size of pectoral muscles remains correlative and the relationship has yet to be tested experimentally.…”
Section: Introductionmentioning
confidence: 99%